Acoustic rhinometric evaluation of the nasal cavity after rapid maxillary expansion - Ribeiro, Annelise Nazareth Cunha; Rino-Neto, José; Paiva, João Batista de (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2018)
Objective: Because of the anatomic proximity between the nasal cavity and the maxilla, much has been investigated regarding changesin nasal geometry after this procedure. In this study, we propose to evaluate the repercussion of RME in the nasal cavity in the patientduring the growth phase. Materials and methods: For this, we evaluated 19 patients with transverse maxillary deficiency and indication for RME. The patientswere evaluated using acoustic rhinometry in 3 moments (pre-RME, post-RME, post-restraint). Results: There was no mean change in MCA1 M1, M2 and M3 (p = 0.122). MCA2 measurement appears to increase in M2. VOL1 is suffering a mean increase in M2 compared to M1 (p = 0.025) and continues higher in M3 (p = 0.271). There is little variationof VOL 2 between the evaluated moments. Conclusion: The results allow us to affirm that RME significantly increases the anterior region of the nasal cavity immediately to theprocedure, however, after the period of containment there is a tendency of recurrence of this increase returning to values close to theinitial cross-sectional area of the nasal cavity.